Manometric investigation of anorectal function in early and late stage Parkinson's disease. Issue 6 (1st June 2000) - Bassotti, Gabrio; Maggio, Dario; Battaglia, Edda; Giulietti, Ornella; Spinozzi, Fabrizio; Reboldi, Gianpaolo; Serra, Anna Maria; Emanuelli, Giorgio; Chiarioni, Giuseppe
Abstract : Abnormal gastrointestinal function is relatively frequent in Parkinson's disease, and constipation is a disturbing symptom in many patients. However, it remains to be established whether anorectal abnormalities are characteristic of the late stages of the disease. Clinical and anorectal manometric function were investigated in groups of early and late stage parkinsonian patients. Thirty one patients (19 men, 12 women, age range 22 to 89 years) entered the study. The disease severity was assessed by Hoehn and Yahr staging: there were four (12.9%) stage I, seven (22.6%) stage II, 10 (32.2%) stage III, and 10 (32.2%) stage IV patients. Anorectal variables were measured by standard manometric equipment and techniques. Values obtained in early stage patients (Hoehn and Yahr stage I and II) were compared with those obtained in late stage patients (Hoehn and Yahr stage III and IV). Overall, more than 70% of patients complained of chronic constipation, with chronic laxative use reported in more than 30%. Late stage patients were slightly older than their early stage counterparts. Pelvic floor dyssynergia was documented in more than 60% of patients. Manometric variables were not different in the two groups. In conclusion, defecatory dysfunction is frequent in Parkinson's disease, it is not confined to late stage patients, and it is found early in the course of the disease. This has potential implications for a targeted therapeutic approach.